Thermotolerance of sunflower inbreds using temperature induction response technique: Thermotolerance of sunflower inbreds using temperature induction response technique - V APARNA; LAKSHMI PRAYAGA; C SARADA; ARTI GUHE (Journal of Oilseeds Research, 2023)
A lab experiment was conducted with 47 sunflower inbreds to evaluate the thermal tolerance at seedling stage using TIR technique. The seedlings are subjected to high temperature stress (HT) with three different temperature treatments control, induction treatment (IT) and lethal treatment (LT). Survival percentage, total seedling length, plumule length, radicle length, seedling weight and seedling vigor index were effected both in IT and LT but the effect was more pronounced in lethal. Based on seed vigor index and percent reduction of total seedling length, inbreds were classified into tolerant, moderately tolerant and susceptible.